Evaluation of the Storage Process as a Prognostic Tool - Jerzy KORCZAK; Dariusz KLOSKOWSKI; Maja WĄCEK (Communications of International Proceedings, 2021)
The study concerns selected aspects of warehouse management. The article presents tools for assessing the warehousing process based on the example of a company with high development potential. The presented results from the analysis of the storage process are an example of an analytical procedure as well as a foundation to develop system assumptions based on in-company IT forecasting tools.
Keywords: Warehouse; Storage Process; Evaluation Of The Storage Process.